Pengaruh Pelatihan dan Budaya Organisasi Terhadap Kompetensi Karyawan PT.(Persero) Pelabuhan Indonesia I Cabang Pekanbaru - Silvayana, Lola; Pramadewi, Arwinence; ', Nuryanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this research to explain the variable training and organizational culture in simultaneous and parcial to competence employee at PT.(Persero) Pelabuhan Indonesia I Cabang Pekanbaru.This research used pimary data namely data were obtained from interviews and administration of the questionnaire to all employees at PT.(Persero) Pelabuhan Indonesia I Cabang Pekanbaru. Secondary data relating to the object and organizational structure. Population in this research were all employees totaling 61 people and wew sampled. Methods of analysis used in this research is the method of multiple linear regression. Of the results of the testing that has been done, simultaneous regression test (uji-F) suggests that training and organizational culture variables simultaneously significant effect on employee competency. Of the partial test (uji- t) results indicate that the variables of training and organizational culture are partially significant efeect on employee competency.results of calculation coefficient of determination is equal to 0,642 which mean, training variables and organizational culture jointly affect the competence of employees is 64,2%, while the remaining 35,8% is influenced by other variables not examined in this research.Keywords : training, organizational culture, and competency employee